Joint amplitude and frequency demodulation analysis based on intrinsic time-scale decomposition for planetary gearbox fault diagnosis. (May 2016) - Feng, Zhipeng; Lin, Xuefeng; Zuo, Ming J.
Abstract: Planetary gearbox vibration signals feature complex modulations, thus leading to intricate sideband structure and resulting in difficulty in fault characteristic frequency identification. Intrinsic time-scale decomposition has unique merits, such as high adaptability to changes in signals, low computational complexity, good capability to suppress mode mixing and to preserve temporal information of transients, and excellent suitability for mono-component decomposition of complex multi-component signals. In order to address the issue with planetary gearbox fault diagnosis due to the multiple modulation sources, a joint amplitude and frequency demodulation analysis method is proposed, by exploiting the merits of intrinsic time-scale decomposition. The signal is firstly decomposed into a series of mono-component proper rotational components. Then the one with its instantaneous frequency fluctuating around the gear meshing frequency or its harmonics is selected as the sensitive component. Next, Fourier transformation is applied to the instantaneous amplitude and instantaneous frequency of the sensitive component to obtain the amplitude and frequency demodulated spectra respectively. Finally, a planetary gearbox fault is diagnosed by matching the peaks in the amplitude and frequency demodulated spectra with the theoretical gear fault characteristic frequencies. The proposed method is illustrated by a numerical simulated signal, and further validated by lab experimental signals of a planetary gearbox. The localized faults of sun, planet and ring gears are diagnosed, showing the effectiveness of the method. Highlights: A joint amplitude and frequency demodulation method is proposed based on ITD. A criterion for electing sensitive PRC is proposed. The sun, planet and ring gear faults are diagnosed. The method is validated experimentally.